A Dematel-Based Method for Prioritizing Strategic Projects Using the Perspectives of the Balanced Scorecard - Oddershede-Herrera, A; Palominos-Belmar, P; Quezada-Llanca, L; Ortiz-Mendez, C (Elsevier B.V., 2022)
This paper presents a method for ranking projects based on their impact on the strategic objectives of the strategy map of the Balanced Scorecard (BSC) of an organization. A strategy map is a visual representation of the strategic objectives and the causal relationships between them in an organization. This work uses this map to align strategic projects to the objectives of the shareholders. Even though there are a large number of articles on the selection/ranking of projects, we found that the literature on the selection/ranking from a strategic perspective is scarce. According to our review, the existing literature does not include any work in which the impact of projects on strategic objectives is established. The work presented here fills this gap. The multicriteria decision-making method DEMATEL is used to rank strategic projects. The method creates a network that includes strategic objectives and projects as nodes and the causal relationships between them. Two types of links between the nodes are included in the model: those representing the direct causal relationships between strategic objectives (strategy map) and those representing the influence of the strategic projects on the strategic objectives. DEMATEL is applied to find the total influence (direct and indirect) of the strategic projects on the strategic objectives of the Financial Perspective of the BSC, which represents the view of the shareholders. The method is illustrated using the case of a real manufacturing company that produces moldings and wall coatings. The managers who participated in the process found it very useful, and the results are being used as a guide for the implementation of strategic projects. The proposed method allows the evaluation of projects in relation to their support to the mission of the organization. © 2022 Elsevier B.V.